A semianalytic time‐resolved poro‐elasto‐plastic model for wellbore stability and stimulation. (30th January 2020) - Fokker, Peter A.; Singh, Aditya; Wassing, Brecht B.T.
Summary: Wellbore stability problems and stimulation operations call for models helping in understanding the subsurface behaviour and optimizing engineering performance. We present a fast, iteratively coupled model for the flow and mechanical behaviour that employs a time‐sequential approach. Updates of pore pressure are calculated in a timestepping approach and propagated analytically to updates of the mechanical response. This way, the spatial and temporal evolution of pressure and mechanical response around a wellbore can be evaluated. The sequential approach facilitates the incorporation of pressure diffusion and of time‐dependent plasticity. Also, it facilitates the implementation of permeability evolving with time, due to plasticity or stimulation. The model has been validated by means of a coupled numerical simulator. Its capabilities are demonstrated with a selection of sensitivity runs for typical parameters. Ongoing investigations target geothermal energy operations through the incorporation of thermo‐elastic stresses and more advanced plasticity models.